Contribution of Contraception to Fertility in the Province of the Special Region of Yogyakarta - Nugraha, Arga; Arsyad, Syahmida S; Nurhayati, Septi (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
The condition of the total fertility rate in Yogyakarta Province has tended to increase in the last decade. But there has also been a decline in the use of modern contraception. This study aims to study the determinant trend between fertility in the Province of Special Region (DI) Yogyakarta using the 2002/03 IDHS data and the 2017 IDHS with aggregate data for women of childbearing age 15-49 years. The results show that the pattern of marriage, the use and effectiveness of contraception, and the pattern of infertility during breastfeeding are intermediate determinants of fertility in DI Yogyakarta Province. Patterns of use and effectiveness of contraception are the main determinants of fertility in the two survey periods. The increasing marital index shows that the reproductive period of women in married status is getting longer and can cause them to be exposed to the possibility of giving birth to more children. The role of the use and effectiveness of contraception is still dominant in contributing to fertility decline. Therefore the use of contraception as a birth control still needs to be strengthened either through advocacy to stake holders in the local government.